Analysis of aliphatic waxes associated with root periderm or exodermis from eleven plant species. (September 2015) - Kosma, Dylan K.; Rice, Adam; Pollard, Mike
Graphical abstract: Alkyl hydroxycinnamates were found to be present in the root waxes of 10 of 11 species analyzed. Reduced forms of the photo-oxidation products of ω-hydroxy oleate and its corresponding dicarboxylate were identified as naturally occurring suberin monomers in rutabaga ( Brassica napus subsp. rapifera) periderm tissues. Highlights: Alkyl hydroxycinnamates are prevalent in the root waxes of many plant species. Alkyl hydroxycinnamates occur in both aerial and subterranean portions of tuberous taproots. Sterols, monoacylglycerols, fatty alcohols and/or fatty acids are typical of root waxes. Reduced photo-oxidation products are native monomer components of rutabaga ( Brassica napus subsp. rapifera) periderm suberin. Abstract: Aliphatic waxes can be found in association with suberized tissues, including roots. Non-polar lipids were isolated by rapid solvent extraction of mature regions of intact roots from eleven angiosperms, including both monocots and dicots. The majority of roots analyzed were taproots or tuberous taproots that had undergone secondary growth and thus were covered by a suberized periderm. The exceptions therein were maize ( Zea mays L.) and rice ( Oryza sativa L.), which present a suberized exodermis. The analysis herein focused on aliphatic waxes, with particular emphasis on alkyl hydroxycinnamates (AHCs). AHCs were widely distributed, absent from only one species, were found in both aerial and subterranean portions of tuberous taproots, and were associated with the fibrous roots of both maize and rice. Most species also contained monoacylglycerols, fatty alcohols and/or free fatty acids. Carrot ( Daucus carrota L.) was the outlier, containing only free fatty acids, sterols, and polyacetylenes as identified components. Sterols were the only ubiquitous component across all roots analyzed. Monoacylglycerols of ω-hydroxy fatty acids were present in maize and rice root waxes. For species within the Brassiceae, wax compositions varied between subspecies or varieties and between aerial and subterranean portions of taproots. In addition, reduced forms of photo-oxidation products of ω-hydroxy oleate and its corresponding dicarboxylic acid (10, 18-dihydroxy-octadec-8-enoate, 9, 18-dihydroxy-octadec-10-enoate and 9-hydroxyoctadec-10-ene-1, 18-dioate) were identified as naturally occurring suberin monomers in rutabaga ( Brassica napus subsp. rapifera Metzg.) periderm tissues.